Inundation mapping using SENTINEL-1 data in the aftermath of super cyclone Amphan : A case study - KUMAR, AMIT; SINGH, ANIL KUMAR; GIRI, R. K.; TRIPATHI, J. N. (MAUSAM, 2021)
Information regarding the extent and severity of inundation resulting because of the landfall of a Tropical Cyclone is required by disaster risk managers in near time to carry out planning and rescue operations. In this regards the Satellite based remote sensing plays a vital role and provides this information to risk managers in near real time. Traditionally Optical data is being used for flood/inundation mapping but it suffers from two constraints : non-availability due to cloud cover and during night time. Microwave SAR data overcomes both these constraints and can provide ground information even during heavy cloud cover and night-time. In this study, inundation mapping of the affected districts of West Bengal due to landfall of Super Cyclone Amphan is attempted by using SAR data from SENTINEL-1 satellite. NOAA Optimum Interpolation Sea Surface Temperature data is also used to carry out the analysis of Bay of Bengal during the genesis and rapid intensification of Super Cyclone Amphan. GsMAP rainfall data is used to carry out rainfall assessment during the landfall of Super Cyclone Amphan. The inundation maps generated using SENTINEL-1 SAR data were validated with the optical images from SENTINEL-2 satellite. The use of SAR data is very crucial for disaster managers in order to plan and execute rescue operations in inundated areas.